Effect of different soil amendments on irrigation and crop yields in the oases of southern Tunisia - Zriba, Zied; Fatma Ezzahra Ben Azaiez; Habib Bousnina; Nissaf Karbout; Habib Lamourou; Mohamed Moussa (Emirates Journal of Food and Agriculture, 2023)
In the oasis agro-system, salinization and hydromorphy are the principal degradation factors that negatively affect the soils. These two processes are the result of the rise of the water table caused by the overdose of irrigations. To counteract soil degradation and restore field productivity, the oasis farmers turn to use sandy and manure amendments. Therefore, three treatments (Control (C), sandy amendment (T1) and combined amendments composed by sand and manure (T2)) has been applied in Nefzaoua oasis to evaluate the effect of different amendments on oasis soil fertility, irrigation parameters, and barley yield. Results showed that T2 enhanced yield parameter (3,07 t/ha) compared to control treatment (1.85 t / ha) thanks to the improvement in the total nitrogen concentration (1.38 g kg -1), soil organic carbon (28.74 g kg- 1) and therefore C / N ratio (20.78) for T2 treatment at the level of the 0-20 cm layer. The results revealed that sand + manure combination (T2) enhanced the irrigation dose that can be effectively applied for the barley plants (19.61 mm) compared to the control treatment (15.49 mm) and T1 treatment (12.26 mm). In addition, the combined treatment T2 declined significantly the oasis soil bulk density leading to rise the porosity of the top layers (0-20 cm). Our results obtained confirmed the effectiveness of the combined amendment composed of sand and manure in improving the fertility and productivity of the amended oasis soil. Keywords: Soil amendments, irrigation, agro-system, soil degradation